2002
DOI: 10.1046/j.1365-2672.2002.01513.x
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and characterization of Lactococcus piscium strains from vacuum-packaged refrigerated beef

Abstract: Aims: To characterize Gram‐positive, catalase‐negative, psychrotrophic, lactic acid‐homofermentative, non‐motile cocci isolated from vacuum‐packaged refrigerated beef using phenotypic and genotypic methods. Methods and Results: A total of 89 strains was isolated at 2 and 6 weeks as one of the predominant microflora of five samples of vacuum‐packaged beef stored at 2°C. The strains were compared with reference strains of some Gram‐positive, catalase‐negative cocci using SDS‐PAGE whole‐cell protein pattern anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
31
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(34 citation statements)
references
References 22 publications
2
31
0
Order By: Relevance
“…1 (groups 1, 2, 3, 8, and 11), both pathogenic and nonpathogenic species are represented. Lactococcus raffinolactis has been reported as a contaminant of food products (36), but a debate on possible confusion with the fish pathogen L. piscium has arisen in more recent studies (35). Such confusion cannot be ruled out, as suggested in Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…1 (groups 1, 2, 3, 8, and 11), both pathogenic and nonpathogenic species are represented. Lactococcus raffinolactis has been reported as a contaminant of food products (36), but a debate on possible confusion with the fish pathogen L. piscium has arisen in more recent studies (35). Such confusion cannot be ruled out, as suggested in Fig.…”
Section: Discussionmentioning
confidence: 99%
“…1) was coinci- T and other type strain cultures maintained in several collections to ATCC HRIA 68, the first culture that was deposited and the most representative of the original description of L. piscium (46). Unlike the isolates described by Sakala et al (35), the type strain is a fastidious organism and is probably the only one ever to have been isolated from diseased fish (46). Our tentative conclusion is that L. raffinolactis and L. piscium are closely related bacteria regularly isolated from fish and food products, sometimes in the clinical context, although any detrimental effect on health is still far from being demonstrated.…”
Section: Discussionmentioning
confidence: 99%
“…Even though two strains of this study originate from late shelf life broiler meat products, the definite role of S. parauberis in spoilage of these products remains unclear. In previous studies, lactococci have been the only homofermentative cocci associated with spoiled meat products (Barakat et al, 2000;Sakala et al, 2002). S. parauberis did not predominate the population in modified atmosphere packaged broiler legs (Björkroth et al, 2005), but almost all strains studied (except LMG 12174 T ) were able to grow at 10°C, and some (RM212.1, RA149.1 and LMG 12173 R ) even at 4°C clearly showing the psychotropic nature of these strains.…”
Section: Discussionmentioning
confidence: 79%
“…The analysis of the tree revealed three major clades within the Lactococcus genus, where L. piscium clustered together with L. garvieae strains, L. raffinolactis, and L. chungangensis. The clustering observed probably reflects niche adaptation, since most of the species in this clade were isolated from animal bodies (50,51) or considered to be environmental (7,10,52,53). While L. garvieae strains appear to be more functionally related to L. piscium than to L. lactis strains based on the gene content, a previous phylogenetic analysis showed that L. garvieae is evolutionarily closer to L. lactis strains than to L. piscium or L. raffinolactis (5).…”
Section: Discussionmentioning
confidence: 84%
“…It was first isolated from a diseased salmonid fish (6) but was later detected in MAP meat products, including beef, poultry, pork, and fish, where it frequently belongs to the predominant microbiota at the end of shelf life. L. piscium has been associated with meat spoilage (3,5,(7)(8)(9), and it was recently also shown to be one of the predominating species in chilled packaged vegetable salads (10).…”
mentioning
confidence: 99%